Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1096/fj.202101812r
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the relationship between plasma and tissue metabolome in a cohort of women with obesity: Analysis of subcutaneous and visceral adipose, muscle, and liver

Abstract: Untargeted metabolomics of blood samples has become widely applied to study metabolic alterations underpinning disease and to identify biomarkers. However, understanding the relevance of a blood metabolite marker can be challenging if it is unknown whether it reflects the concentration in relevant tissues. To explore this field, metabolomic and lipidomic profiles of plasma, four sites of adipose tissues (ATs) from peripheral or central depot, two sites of muscle tissue, and liver tissue from a group of nondiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 73 publications
1
1
0
2
Order By: Relevance
“…We anticipated that such trends would exist because tissues balance metabolites in different manners. 62,63 Our results provide evidence to support this hypothesis. Of the 12 types of modifications analyzed in this study, five were found to be differentially abundant in the gills.…”
Section: Metabolite Concentrations In Tissues May Uphold Global Level...supporting
confidence: 76%
See 1 more Smart Citation
“…We anticipated that such trends would exist because tissues balance metabolites in different manners. 62,63 Our results provide evidence to support this hypothesis. Of the 12 types of modifications analyzed in this study, five were found to be differentially abundant in the gills.…”
Section: Metabolite Concentrations In Tissues May Uphold Global Level...supporting
confidence: 76%
“…In this study, we evaluated whether specific types of modifications, such as acetylation, were consistently more abundant or less abundant in certain tissues. We anticipated that such trends would exist because tissues balance metabolites in different manners. , Our results provide evidence to support this hypothesis. Of the 12 types of modifications analyzed in this study, five were found to be differentially abundant in the gills.…”
Section: Discussionmentioning
confidence: 99%
“…Особое внимание следует уделить исследованию 2022 г., в котором 26 пациентов с ожирением без СД2 прошли бариатрическую операцию [63]. У пациентов получены биоптаты подкожной жировой ткани бедра, подкожной жировой ткани живота, глубокой подкожной жировой ткани живота, внутрибрюшной жировой ткани, двух участков мышечной ткани (васта латеральная мышца, прямая мышца живота) и печени (клин правой доли).…”
Section: сравнение подкожного и висцерального жираunclassified
“…Печень является основным источником церамидов, но учитывая, что их содержание в печени хорошо коррелирует с плазменными фракциями, доказывает тот факт, что сфинголипипиды в плазме могут отражать их аномальный метаболизм в печени. Сфингомиелины, которые содержали более низкое четное общее количество углерода (C ≤ 34) и мононенасыщенную цепь жирных кислот, а также их концентрация коррелировали с показателями внутрибрюшной жировой ткани, печени и мышц [63].…”
Section: сравнение подкожного и висцерального жираunclassified